Managing the medical resources of a national insurance program: lessons based on China's NCMS - Wenqiang Qian; Xiangyu Cheng (BMC, 2022)
Abstract Background The security of medical insurance fund is very important to health equity. In China, the expenditure of medical insurance fund has increased sharply year after year, and the balance of local medical insurance fund is difficult to sustain. To realize the equitable distribution of the medical insurance burden, the central government has to continuously increase transfer payments, which causes regional unfairness in the distribution of central financial resources. This paper explores the influence of central transfer payments on the balance of medical insurance fund, influential mechanisms, and the strategic behavior of local governments. Methods First, we constructed a dynamic game model between central government and local governments and analyzed the mechanism of central transfer payments affecting the balance of local medical insurance fund. Then, based on the provincial panel data of 28 provincial administrative regions in China from 2004 to 2014, an empirical test was made. The spatial regression model was constructed, and the transfer payments obtained by neighboring provinces in the previous year were taken as instrumental variables. Results Central transfer payments led to strategic behaviors by local governments that resulted in increased local health insurance fund expenditures and lower balance rates. Moreover, the central transfer payments demonstrated "path dependence". Central transfer payments had a significant negative influence on the local NCMS fund balance rate. The local government subsidy and per capita GDP had a significant positive impact on the local NCMS fund balance rate. The obtained transfer payments of local governments had a significant space correlation. This study based on NCMS data remains valid. Conclusions Central transfer payments induced the strategic behavior of local governments, which neglected to supervise the expenditure of medical insurance fund, reducing the efficiency of medical insurance fund management and use. The financial resources of medical insurance fund are unevenly distributed among provinces. Measures such as strengthening the supervision ability and initiatives of local governments, refining the central transfer payment mechanism, promoting the economic growth of western regions, and increasing rates for individual contributions appropriately can ensure that the medical insurance fund are used well and distributed equitably.